One new species of Melita Leach, 1814 (Hadzioidea, Melitidae) from Gujarat State, India - Thacker, Dimple; Myers, Alan A.; Trivedi, Jigneshkumar N. (Zootaxa, 2025)
In the present study, a new species, Melita ajmali sp. nov. is described on the basis of specimens collected from Gujarat State, India. This new species is differentiated from the closely related species M. persia Momtazi, Sari & Maghsoudlou, 2014, by its comparatively longer accessory flagellum, the inner ramus of uropod 3 with 3 apical setae and epimeron 3 with smooth posterior margin.